2004
DOI: 10.1007/s11187-004-3991-8
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurship and Development: The Role of Clusters

Abstract: Defining entrepreneurship as the creation of new organisations,this paper explores,from a literature review standpoint,the moderating effect of clusters on the impact of entrepreneurship on development. To identify potential causes of this moderating effect, the paper focuses on three different impacts: entrepreneurship on development, clusters on development,and clusters on entrepreneurship. The findings of the paper are threefold.First,entrepreneurship is positively associated with economic growth.Given the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
168
0
21

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 224 publications
(190 citation statements)
references
References 88 publications
1
168
0
21
Order By: Relevance
“…Rocha, 2004 for a review), the contextual approach to entrepreneurship has long been discussed primarily from the perspective of the national economy. This volume offers theoretical arguments, empirical evidence and policy-based comments to support the hypothesis that entrepreneurial activities are to a large extent a "regional event" (Feldman, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Rocha, 2004 for a review), the contextual approach to entrepreneurship has long been discussed primarily from the perspective of the national economy. This volume offers theoretical arguments, empirical evidence and policy-based comments to support the hypothesis that entrepreneurial activities are to a large extent a "regional event" (Feldman, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Empirical evidences confirmed that, despite in the developed economies, the linear roadmap of entrepreneurship, business competitiveness and economic capability dominates the mainstream of literature, however, such a positive linearity is not significant in developing economies (Hector & Rocha, 2004), and that the trajectory from entrepreneurship to industrial clusters and economic growth, is leveraged by regional technological capability of innovation, which serves as a platform to facilitate industrial transformation and corporate productivity (Feldman & Yoon, 2012). For example, by comparing the diverged path of entrepreneurship between Silicon Valley, CA and Route 128, MA, the two global hubs of technological innovation in the IT-industries, some scholars found that, the sharply contrasted outcome between the two locations since the 1960s, may be attributed to their respectively differentiated path of industrial cultures, inter-firm relations and organizational capability of innovation (Kenney & Burg, 1999).…”
Section: The Barriers Hindering the Sustainable Development Of Chintrmentioning
confidence: 77%
“…Les structures en réseau sont considérées par plusieurs auteurs comme de véritables instruments de politique éco-nomique en raison de leurs impacts positifs sur la performance des entreprises, la compétitivité et la croissance économique nationale (Rocha, 2004). En effet, on leur attribue plusieurs vertus telles que la flexibilité et la réactivité.…”
Section: Résumé De L'articleunclassified
“…La coopération devient ainsi un élé-ment important de stratégie et d'organisation pour ces entreprises. Cette coopération implique une réorganisation plus souple des structures organisationnelles, plus précisément le développement des structures en réseau (Miles et Snow, 1986).Les structures en réseau sont considérées par plusieurs auteurs comme de véritables instruments de politique éco-nomique en raison de leurs impacts positifs sur la performance des entreprises, la compétitivité et la croissance économique nationale (Rocha, 2004). En effet, on leur attribue plusieurs vertus telles que la flexibilité et la réactivité.…”
unclassified